2013
DOI: 10.1038/bcj.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs and microRNA machinery in the pathogenesis of diffuse large B-cell lymphoma

Abstract: Deregulation of microRNA (miRNA) expression has been documented in diffuse large B-cell lymphoma (DLBCL). However, the impact of miRNAs and their machinery in DLBCL is not fully determined. Here, we assessed the role of miRNA expression and their processing genes in DLBCL development. Using microarray and RT-qPCR approaches, we quantified global miRNAs and core components of miRNA-processing genes expression in 75 DLBCLs (56 de novo and 19 transformed) and 10 lymph nodes (LN). Differential miRNA signatures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 59 publications
(91 reference statements)
4
58
0
Order By: Relevance
“…MiR-126-3p and miR-145-4p are known to be down-regulated in B-cell malignancies, such as chronic lymphocytic leukemia and diffuse large B-cell lymphoma, respectively. 49,50 Moreover, autoantibodies are frequently detected in patients with AA. 51,52 Perhaps dysregulations of B cells is related to aberrant B-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-126-3p and miR-145-4p are known to be down-regulated in B-cell malignancies, such as chronic lymphocytic leukemia and diffuse large B-cell lymphoma, respectively. 49,50 Moreover, autoantibodies are frequently detected in patients with AA. 51,52 Perhaps dysregulations of B cells is related to aberrant B-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although overexpression of MYC is driven by an immunoglobulin gene enhancer generally associated with BL, recurrent genetic abnormalities apart from MYC are reported. Abnormalities of chromosomes 1, 6, 7, 13, 17 and 22 are reported in pediatric BL [23][24]. In studies of BL samples, cytogenetic abnormalities have been reported.…”
Section: Burkitt Lymphomamentioning
confidence: 99%
“…Previous studies have confirmed that miRs are involved in the pathogenesis of DLBCL (17,18). In 2009, Li et al (19) used a miR chip method to analyze the expression of pathological tissues from 59 patients with DLBCL and 26 types of existing DLBCL cell lines.…”
Section: Functions and Targets Of Dysregulated Mirs In Dlbclmentioning
confidence: 99%